Motivation of Students Learning Indonesian as a Foreign Languag in BIPAS: An In-Country Learning Program at Udayana University in Bali - Anak Agung Sagung Shanti Sari Dewi; Ni Luh Ketut Mas Indrawati; Ketut Artawa; Ni Luh Nyoman Seri Malini (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Student motivation is crucial to success in learning a foreign language. This study focuses on analyzing the motivation of students studying Indonesian as a foreign language in the Bipas in-country learning program at Udayana University in Bali. Specifically, the study is aimed at investigating the motivations of foreign students learning Indonesian in the program, and whether students' learning motivation shifts by the end of the course. The study involved 38 foreign students and five Indonesian lecturers during the Spring 2024 semester as respondents, and applied an explanatory sequential mixed methods design which consists of two phases, namely a quantitative phase and a qualitative phase to collect data. The results show that, despite strong support from the Balinese community for using the Indonesian language, students' motivation shifted from instrumental to integrative at the end of the course. Integrative motivation, which is prevalent, is defined as a desire to connect with the culture and community. Instrumental motivation ,on the other hand, such as the expectation that learning Indonesian will open up career opportunities or improve social status, remains relatively low. To increase overall motivation, the learning programme should combine the two types of motivation, strengthening the sense of social connection and emphasising the practical value and tangible benefits of learning Indonesian.